More answers

The expression βsix minus one times zero add two divided by twoβ can be simplified using the order of operations (PEMDAS). First, we would multiply one by zero, which is zero. Then, we would divide two by two, which equals one. Finally, we would subtract zero from six and add one, resulting in the answer of seven.

Q: What is six minus one times zero add two divded by 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-6 x -3 = 18 + (-6) = 12

The answer is 44. -6 * -11 = 66 66 + -22 = 44

x = 10 Minus 6 times 10 = minus 60 Add 3 to minus 60 = minus 57

Perhaps you mean minus minus one is plus one. Like subtracting (taking away) a debt is equivalent to adding on. If you bank balance is two dollars in the red (debt) if you add 2 dollars, that debt has gone. minus 2 minus minus 2 is zero, same as minus 2 plus 2 is zero.

it is 10 times larger (of the number that was multiplied by 10 or added a zero at the end)

Related questions

adding one to minus one = zero.

-6 x -3 = 18 + (-6) = 12

The answer is 44. -6 * -11 = 66 66 + -22 = 44

x = 10 Minus 6 times 10 = minus 60 Add 3 to minus 60 = minus 57

Perhaps you mean minus minus one is plus one. Like subtracting (taking away) a debt is equivalent to adding on. If you bank balance is two dollars in the red (debt) if you add 2 dollars, that debt has gone. minus 2 minus minus 2 is zero, same as minus 2 plus 2 is zero.

Add minus times divide

2+2+2=6 6/2=3

8 times 2 is 16, and add a zero, so its 160

I steal five dollars from you: minus $5. I steal five more dollars from you: minus $10. If those two minuses canceled, you would be minus zero. They don't cancel: you add up the numbers, but it's all minus.

Undefined: You cannot divide by zero

it is 10 times larger (of the number that was multiplied by 10 or added a zero at the end)

It's 9z-7. because: you do the 8 times z first (8z) then add the z, (9z), then minus 7. 9z-7